Behavioral and Brain Structural Changes in Kindled Rats Induced by Coriaria Lactone/Pentylenetetrazol - He, Shixu; Qiu, Xiangmiao; Wang, Jing; Yang, Linghui; Peng, Anjiao; Li, Wanling; Dong, Bosi; Tang, Yusha; Lai, Wanlin; Chen, Lei (Frontiers in Behavioral Neuroscience, 2021)
Epilepsy is a common chronic neurological disease that is characterized by spontaneous seizures and is commonly comorbid with behavioral and mood disorders. No studies have yet examined the behavioral or structural brain changes associated with coriaria lactone (CL)-induced and pentylenetetrazol (PTZ)-induced kindling. This study examined whether the increased seizure susceptibility induced by CL/PTZ is accompanied by behavioral impairments, and aimed to identify associated structural brain changes. Kindling models were induced using CL and PTZ, with 10 rats in each group. After successful kindling, rats were subjected to brain structural imaging using T2-weighted imaging, and underwent behavioral tests, including the open field test, water maze tasks, and contextual fear conditioning. Voxel-based morphometry was used to identify possible brain structural changes associated with kindling and/or behaviors. Support-vector machine learning was applied for the integrative analysis of behavioral changes and structural brain imaging. In the open field test, both the CL (P = 0.040) and PTZ groups (P = 0.002) spent more time in the central area than did the control group. Only the PTZ group (50.29 ± 29.56 s) showed a freezing time that was significantly less than that of the control group (94.8 ± 41.04 s; P = 0.024, Tukey’s HSD-corrected) in contextual fear conditioning, which is suggestive of an impaired fear-associated learning ability. Brain imaging analysis revealed that gray matter volume (GMV) of the hippocampus changed in both the CL and PTZ groups compared to control. The support-vector machine learning model indicated that the retrosplenial dysgranular cortex and primary somatosensory cortex were associated with both two kindling models. Furthermore, the support-vector regression model results indicated that kindling-associated GMV changes can be used to predict general exploratory activity in open field test. In conclusion, this is the first study to report greater general exploratory activity in a CL-induced kindling model. Moreover, the general exploratory activity in the open field test can be predicted by GMV of brain regions associated with kindling.